Fiber Reinforcement in Polymer Composites: A Comprehensive Review of Material Properties and Applications - Dr. Anil Kumar Rao; Rameswara Reddy Yeddula; Dr. Tasneem K. H. Khan; Dr.P.Krishnan; Dr.B.Sridevi; Dr. Sneha Khadse (The Bioscan, 2025)
One of the most popular areas that have received a lot of focus concerns fiber-reinforced polymer composites (FRPs) that have desirable, naturally high mechanical characteristics, light weight, and flexibility in multiple applications. High-strength fibers, i.e. glass, carbon, and natural fibers with polymer matrix leads to the development of materials with unmatched mechanical and thermal properties. These composites are widely utilized in such industries such as automotive, aerospace industry, constructions, and the sports industry. This paper draws a critical review on fiber reinforced polymer composites with emphasis on fiber type, material characteristic, fabrication method and uses. The review examines the variations between the natural and synthetic fiber with focus on the merits and the problem facing each. It is shown that the use of natural fiber, in general, is especially interesting since it is sustainable, cost-effective, and biodegradable. Moreover, the paper explains the processing techniques which include, hand lay-up, resin transfer molding and compression molding and these techniques are paramount towards defining the final composite propriety. The epilogue of the paper reviews the present and future possibilities of fiber-reinforced composites and explains new directions in this field within the substitution of hybrid composites and the achievement of nanotechnology in solving material challenges.